Perbedaan Derajat Aglutinasi Uji Golongan Darah Berdasarkan Teknik Penanganan Sampel dalam Pembuatan Suspensi Sel Darah Merah - Lucia Sincu Gunawan; Rumeyda Chitra Puspita (Biomedika, 2019)
Pre transfusion testing is a very essential part of blood transfusion procedure. In some types of pretransfusion test, suspension of red blood cells is required. This cell suspension is made to optimize the antigen-antibody reaction so that the on going reaction can be clearly observed. The practice of determining blood type needs a suspension of red blood cells, which its washing phase is a time-consuming. The type of sample used can be whole blood with anticoagulants or frozen blood samples. Due to time constraints, the standard procedures were modified. This study aimed to determine the differences in the degree of agglutination of blood type testing based on the handling samples’ techniques in the manufacture of red blood cell suspensions. Blood group testing was done by the tube method on venous blood samples with different sample handling techniques: frozen blood samples without anticoagulants with storage, fresh blood samples with direct addition of 0.9% NaCl, and EDTA anticoagulant blood samples with refrigerator storage 8 - 24 hours at 40C. The number of samples for each type of treatment is 30 samples, and an assessment of the degree of agglutination in the blood group test is carried out by 2 analysts. There were differences in the mean degree of aglutination between the 3 suspensi-making techniques with NaCl samples (Mean = 3.88; SD = 0.32), frozen samples (Mean = 3.93; SD = 0.25), and EDTA samples (Mean = 3.98; SD = 0.13), but the mean differences was not statistically significant (p> 0.05), so it can be concluded that the three types of samples could be used to replace one another as a comparable sample alternative in making red blood cell suspension to measure ABO cell grouping method.